Laser welded body

By adding a laser absorber to the liquid crystal resin, the problem of difficulty in laser welding of liquid crystal resin is solved, and a high-strength welding effect with low energy consumption is achieved.

JP2025019809APending Publication Date: 2025-02-07ORIENT CHEM INDS
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023123637
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-28
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Due to the extremely low laser transmissibility of liquid crystal resins, it is difficult to achieve effective conduction of laser light by thinning the thickness of resin members and adding a large amount of filler, resulting in the inability to enter the internally and generate heat during laser welding, and the inability to achieve effective welding.

Method used

A laser absorber, such as nigrosine and/or carbon black, is added to the liquid crystal resin to form a resin member containing 0.001% to 0.48% of the laser absorber, and welding is achieved by laser irradiation at the joint site.

Benefits of technology

Even under low output laser, heat can be generated effectively, welding and cooling of resin members can be achieved, forming an integral welded body, improving welding strength and saving energy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025019809000001_ABST
    Figure 2025019809000001_ABST
Patent Text Reader

Abstract

To provide a laser welded body which is integrated by adding a laser beam absorbent, which is a laser absorbing dye, to a thermoplastic resin containing a liquid crystal resin and which enables laser welding even when resin members containing a liquid crystal resin are butted together.SOLUTION: In a laser welded body in which resin members containing a thermoplastic resin and a laser beam absorbent are laser welded together at least at a portion of a butt joint where at least a portion of ends of the resin members are butted together, the thermoplastic resin contains a liquid crystal resin, and the laser beam absorbent is contained in the resin members in the amount of 0.001 mass% to 0.48 mass%.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laser welded article obtained by butting ends of resin members made of a thermoplastic resin and a laser beam absorbent together and irradiating the butted portion with laser beam to form a single body. [Background technology]

[0002] Lightweight thermoplastic resin products are often used instead of metals in parts used in vehicles in the transportation field, such as automobiles and railways, and in structural parts in the electronic and electrical equipment field. Laser welding is known as a method for joining such thermoplastic resin members together.

[0003] Some of the features of laser welding are that it is possible to weld plastic components simply by irradiating the area to be joined locally with laser light; because heat is generated locally, there is minimal thermal impact on surrounding areas other than the welded area; it does not produce mechanical vibration; it is possible to weld plastic components with fine details or three-dimensional, complex structures; it is highly reproducible; it can maintain high airtightness; it has high joint strength; the seams of the welded areas are not noticeable; and it does not produce dust.

[0004] Laser welding can reliably weld resin components and firmly join them. Furthermore, it can provide a joining strength equal to or greater than that achieved by fastening with fastening parts (bolts, screws, clips, etc.) or by joining with adhesives, vibration welding, ultrasonic welding, and other methods. Moreover, laser welding can minimize the effects of heat without causing vibration, and can therefore achieve labor savings, improved productivity, and reduced manufacturing costs. For this reason, laser welding is suitable for joining functional parts and electronic parts that must be protected from the effects of vibration and heat in, for example, the automotive industry and the electrical and electronics industry, and can also be used to join resin parts with complex shapes.

[0005] Patent Document 1 discloses a laser welded body by the present inventors, in which weakly laser-absorbent resin members containing a thermoplastic resin and a weakly laser-absorbent material are butted together and integrated by irradiating the butted portion with laser light. As thermoplastic resins, polyamide resins, polycarbonate resins, polyphenylene sulfide resins, polybutylene terephthalate resins, and polypropylene resins are disclosed, but all of these are resins that easily transmit laser light, and there are no examples of using liquid crystal resins.

[0006] In addition, liquid crystalline resins have good fluidity and dimensional stability because the molecular chains are aligned in parallel in the molten state and are less entangled, and also have excellent mechanical strength, so their applications have expanded in recent years. In particular, because of their high fluidity, they are molded into small parts, and their use in electrical and electronic parts has attracted attention.

[0007] Patent Document 2 discloses a laser welded body in which a container made of a molding material containing liquid crystal polyester as a thermoplastic resin and a lid made of a light-transmitting material are used, and the space surrounded by the side walls and bottom of the container is sealed with the lid, and a laser beam is irradiated to the contact portion between the top of the side wall and the lid to integrate them. In this laser welded body, the laser beam is irradiated to the overlapping portion of the top of the side wall and the lid, and there is no description of butting the ends together and irradiating the butted portion with a laser beam to integrate them. In addition, it is necessary to separately adjust the resin member that transmits the laser beam and the resin member that absorbs the laser beam.

[0008] Patent Document 3 discloses a laser welded body using a laser light transmitting member formed from a liquid crystal resin composition for laser welding containing 5 to 230 parts by mass of a reinforcing agent relative to 100 parts by mass of a liquid crystal resin, and the laser welded body is formed by shaping the liquid crystal resin composition for laser welding and using a laser light transmitting member having a thickness of 0.05 to 2.0 mm in the transmitting portion of the laser welded portion. This laser welded body is a laser welded body in which a laser light transmitting member is superimposed on a laser light absorbing member, and the superimposed portion is irradiated with laser light to be integrated, but there is no description of butting the ends together and irradiating the butted portion with laser light to integrate them. In addition, it is necessary to separately prepare the resin member that transmits laser light and the resin member that absorbs laser light. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] International Publication No. 2007 / 034978 [Patent Document 2] JP 2013-203026 A [Patent Document 3] JP 2004-292526 A Summary of the Invention [Problem to be solved by the invention]

[0010] As shown in the above Patent Documents 2 and 3, liquid crystal resins have extremely low laser light transmittance. Therefore, in order to transmit laser light, it is necessary to reduce the thickness of the transmitting resin member or to use a large amount of filler. However, in butt welding, in which the ends of resin members are butted together and laser light is irradiated onto the ends, the laser light needs to penetrate the inside, but with liquid crystal resins, the laser light does not reach the inside, and there is a problem that insufficient heat is generated and a laser welded body cannot be obtained.

[0011] The present invention has been made to solve the above-mentioned problems, and aims to provide a laser-welded body in which resin parts containing liquid crystalline resin can be butted together and laser welded to one another by adding a laser light absorbent, which is a laser light absorbing dye, to a thermoplastic resin containing a liquid crystalline resin. [Means for solving the problem]

[0012] The laser-welded product of the present invention, made to achieve the above-mentioned object, is a laser-welded product in which resin members containing a thermoplastic resin and a laser beam absorbent are laser-welded together at least a portion of a butt joint where at least a portion of the ends of the resin members are butted together, the thermoplastic resin containing a liquid crystalline resin, and the laser beam absorbent is contained in the resin members in an amount of 0.001% by mass to 0.48% by mass.

[0013] In this laser welded article, the thermoplastic resin may contain a liquid crystal polyester.

[0014] In this laser welded article, the laser light absorbing agent is preferably nigrosine and / or carbon black.

[0015] In the laser welded article, the laser light absorbing agent is preferably nigrosine, and is contained in the resin member at 0.03% by mass to 0.48% by mass.

[0016] In the laser welded article, the laser light absorbing agent is preferably carbon black, and is contained in the resin member at 0.001% by mass to 0.064% by mass.

[0017] The laser welded article may have a single resin member or multiple resin members.

[0018] It is also preferable that the laser welded article includes a plurality of resin members, and the laser beam absorbent in at least one of the resin members is nigrosine.

[0019] It is also preferable that the laser welded article has a plurality of resin members, and the laser beam absorbent in at least one of the resin members is carbon black. Effect of the Invention

[0020] The laser welded product of the present invention is obtained by butting together the ends of resin members made of a liquid crystalline resin and a laser beam absorbent, and irradiating the butted parts with laser beam to integrate them. Although the liquid crystalline resin has an extremely low transmittance of laser beam and is not suitable for laser welding, by including a laser beam absorbent, even a small amount of laser beam that penetrates the resin can efficiently generate heat, melt the resin, and then cool and solidify it to obtain an integrated laser welded product.

[0021] Furthermore, by increasing the content of the laser light absorbing material, it is possible to obtain a laser welded product even with a weaker laser light output, which is also excellent in terms of energy saving. [Brief description of the drawings]

[0022] [Figure 1] 1A to 1C are views showing the process of manufacturing a laser welded body to which the present invention is applied by butting ends of a plurality of resin members together. [Diagram 2] 1A to 1C are views showing the process of manufacturing a laser welded body to which the present invention is applied by bending and butting a single resin member. [Diagram 3] 1A to 1C are views showing the process of manufacturing a laser welded body to which the present invention is applied by bending and butting a single resin member. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] Hereinafter, embodiments for carrying out the present invention will be described in detail, but the scope of the present invention is not limited to these embodiments. In this specification, the symbol "to" is used to mean that the numerical values ​​before and after the symbol "to" are included as the lower limit and upper limit.

[0024] An example of the laser welded article of the present invention will be described in detail below with reference to FIG. 1 corresponding to the embodiment.

[0025] To manufacture the laser welded body of the present invention, for example, a plurality of resin members 1 and 2 molded into a plate shape are used. Both of the resin members 1 and 2 contain at least a liquid crystal resin and a laser beam absorbent. The ends of these resin members are butted together, and the butted parts are irradiated with a laser beam 3. The liquid crystal resin has an extremely low laser beam transmittance, so the laser beam 3 can hardly penetrate into the inside, but since it contains a laser beam absorbent, it can generate heat even with a small amount of laser beam. This melts the resin, forming a welded part 4 and becoming one body. Since the laser beam is directly irradiated to the resin members containing the laser beam absorbent, it is important that the output conditions are adjusted so that heat is generated within a range that does not cause burns or voids in the irradiated parts, and the resin is melted.

[0026] More specifically, the laser welded body is formed by laser welding these resin members together at least at a part of the butt joint where at least a part of the ends of the resin members are butted together. The butt joint does not have to be the entire end, and the welded part 4 does not have to be the entire butt joint. The resin members can be laser welded by containing the laser beam absorbent in an amount of 0.001% by mass to 0.48% by mass in the resin members.

[0027] When the resin members 1 and 2 are butted together to form a butted portion in order to obtain a laser welded body, a suitable jig may be used to apply pressure to fix them in place. Furthermore, a member having a cooling effect may be disposed.

[0028] 2 and 3, a single flexible resin member 1 may be used to produce a laser welded product as shown in Fig. 2. The single resin member 1 is formed by molding a liquid crystalline resin containing a laser beam absorbent, as described above. This resin member 1 is bent and rolled, and at least one or more of both ends are butted together to form a butted portion, and at least a part of the butted portion is irradiated with laser beam 3 to obtain an integrated laser welded product.

[0029] When the resin members 1 are bent and butted together to form the butted portion, pressure may be applied using an appropriate jig to fix them in place. A member having a cooling effect may also be disposed. The resin member 1 may be formed into a roll or a cylinder.

[0030] The laser-welded article of the present invention may be in the form of a plurality of flat plates of uniform thickness as described above, or a single flexible shape, and may have any shape such as a roll, cylinder, prism, box, etc., formed by molding with a mold, or curved or bent.

[0031] Conventional laser welded products using liquid crystalline resins are welded products in which a laser-transmissible member and a laser-absorbent member are overlapped and integrated by irradiating a laser beam from the laser-transmissible member side. In contrast, the laser welded product of the present invention is a laser welded product in which a liquid crystalline resin and a resin member containing a laser-absorbent are butted together and integrated by irradiating the butted portion with a laser beam, and has sufficient weld strength.

[0032] The laser welded product of the present invention exhibits a strength of at least 50 N or more in a tensile test in accordance with JIS K-7161:2014, and preferably exhibits a strength of 100 N or more.

[0033] As the laser beam used for laser welding, an infrared ray of 800 to 1600 nm, which is a wavelength region longer than visible light, is used, preferably a laser beam having an oscillation wavelength of 800 to 1100 nm. For example, a solid-state laser (Nd:YAG excitation, semiconductor laser excitation, etc.), a semiconductor laser, a tunable diode laser, or a titanium sapphire laser (Nd:YAG excitation) is used. In addition, a halogen lamp or a xenon lamp that generates infrared rays with a wavelength of 700 nm or more may be used. In addition, the laser beam may be irradiated to the surface of the resin member from a vertical direction or an oblique direction, and may be irradiated from one direction or multiple directions (for example, the laser beam is irradiated from both sides of the joining surface). The output of the laser beam is appropriately adjusted according to the scanning speed and the absorption capacity of the resin member.

[0034] When using halogen lamps that generate infrared rays with wavelengths of 700 nm or more, the lamps are often arranged in a strip shape. Examples of the irradiation mode include a scanning type in which the lamp irradiation part moves, a masking type in which the welding material moves, and a type in which the lamps simultaneously irradiate the welding material from multiple directions. The irradiation can be performed by appropriately adjusting the infrared irradiation width, irradiation time, irradiation energy, etc. Since halogen lamps have an energy distribution centered on the near-infrared region, energy may exist on the short wavelength side of the energy distribution, i.e., in the visible region. In such cases, welding marks may be generated on the surface of the material, so the visible region energy may be blocked using a cut filter or the like.

[0035] The spot diameter of the laser light is preferably 3 mm to 5 mm. If it is less than 3 mm, the energy becomes excessive and burning is likely to occur, whereas if it exceeds 5 mm, the energy is dissipated, sufficient heat generation does not occur, and a welded body cannot be obtained.

[0036] Next, the resin member will be described in more detail.

[0037] The liquid crystal resin used in the present invention is a resin capable of forming an anisotropic melt phase, and is preferably a liquid crystal polyester or a liquid crystal polyesteramide having an ester bond. For example, liquid crystal polyesters consisting of structural units selected from aromatic oxycarbonyl units, aromatic dioxy units, aromatic and / or aliphatic dicarbonyl units, alkylenedioxy units, etc. and forming an anisotropic melt phase, or liquid crystal polyesteramides consisting of the above structural units and structural units selected from aromatic iminocarbonyl units, aromatic diimino units, aromatic iminoxy units, etc. and forming an anisotropic melt phase, can be mentioned.

[0038] Specifically, liquid crystalline polyesters comprising structural units generated from p-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid; liquid crystalline polyesters comprising structural units generated from p-hydroxybenzoic acid, structural units generated from 6-hydroxy-2-naphthoic acid, and structural units generated from aromatic dihydroxy compounds and / or aliphatic dicarboxylic acids; liquid crystalline polyesters comprising structural units generated from p-hydroxybenzoic acid, structural units generated from 4,4'-dihydroxybiphenyl, and structural units generated from aromatic dicarboxylic acids such as terephthalic acid and isophthalic acid and / or aliphatic dicarboxylic acids such as adipic acid and sebacic acid; liquid crystalline polyesters comprising structural units generated from p-hydroxybenzoic acid, structural units generated from ethylene glycol, and structural units generated from terephthalic acid; liquid crystalline polyesters comprising structural units generated from p-hydroxybenzoic acid, structural units generated from ethylene glycol, structural units generated from terephthalic acid, and isophthalic acid. Liquid crystalline polyesters include liquid crystalline polyesters consisting of structural units generated from p-hydroxybenzoic acid, structural units generated from ethylene glycol, structural units generated from 4,4'-dihydroxybiphenyl, structural units generated from terephthalic acid and / or aliphatic dicarboxylic acids such as adipic acid and sebacic acid; liquid crystalline polyesters consisting of structural units generated from p-hydroxybenzoic acid, structural units generated from ethylene glycol, structural units generated from aromatic dihydroxy compounds, and structural units generated from aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, and 2,6-naphthalenedicarboxylic acid. Liquid crystalline polyester amides include polyester amides that form an anisotropic molten phase and contain p-iminophenoxy units generated from p-aminophenol in addition to structural units selected from aromatic oxycarbonyl units, aromatic dioxy units, aromatic and / or aliphatic dicarbonyl units, alkylenedioxy units, etc.

[0039] As liquid crystalline polyesters, Sumikasuper (registered trademark) LCP manufactured by Sumitomo Chemical Co., Ltd., UENO LCP (registered trademark) manufactured by Ueno Pharmaceutical Co., Ltd., LAPEROS (registered trademark) manufactured by Polyplastics Co., Ltd., and the like are available.

[0040] Liquid crystal polyesters are classified into types I, II, and III in order of heat resistance. Of these, types I and II, which can withstand the temperature of solder reflow, are mainstream. Of course, the laser welded article of the present invention can be obtained in all types I, II, and III.

[0041] As an example of the I type liquid crystalline polyester, Sumikasuper (registered trademark) LCP E6007LHF manufactured by Sumitomo Chemical Co., Ltd., etc. are commercially available. As an example of the II type liquid crystalline polyester, UENO LCP (registered trademark) 3030G manufactured by Ueno Pharmaceutical Co., Ltd., LAPEROS (registered trademark) E130i manufactured by Polyplastics Co., Ltd., etc. are commercially available.

[0042] Liquid crystal polyester is a resin with low laser light transmittance. For example, a 1 mm thick molded plate has a transmittance of 10% or less for 940 nm laser light.

[0043] Examples of the laser light absorbent contained in the resin workpiece include azine compounds, nigrosine, aniline black, carbon black, phthalocyanine, naphthalocyanine, porphyrin, cyanine compounds, perylene, quaterrylene, metal complexes, azo dyes, anthraquinone, squaric acid derivatives, immonium dyes, etc. Among these, nigrosine and carbon black are particularly preferred.

[0044] Nigrosine includes black azine-based condensation mixtures such as those described in the COLOR INDEX as CISOLVENT BLACK 5 and CISOLVENT BLACK 7. Among them, CISOLVENT BLACK 7 is more preferable. Such nigrosine can be synthesized, for example, by oxidizing and dehydrating condensation of aniline, aniline hydrochloride, and nitrobenzene in the presence of iron chloride at a reaction temperature of 160 to 180°C. As such nigrosine, the product name NUBIAN BLACK series manufactured by Orient Chemical Industry Co., Ltd. is commercially available.

[0045] The content of nigrosine in the resin member is 0.03 to 0.48% by mass, preferably 0.03 to 0.24% by mass. If the content is less than 0.03% by mass, the heat generated is small even when the energy of the laser light is absorbed, so the temperature does not rise sufficiently and the welding strength of the joint between the resin members is low. If the content exceeds 0.48% by mass, the heat generated is too high, scorching and voids are likely to occur, and it is difficult to obtain sufficient welding strength between the resin members.

[0046] Carbon black that can be used is generally commercially available. Specifically, when classified according to pH, any of acidic carbon black, neutral carbon black, and basic carbon black can be used, and when classified according to manufacturing method, any of furnace type carbon black, channel type carbon black, acetylene type carbon black, and thermal type carbon black can be used.

[0047] Specific examples of carbon black used in the present invention include #990, MA600, and #40 manufactured by Mitsubishi Chemical Corporation, Color Black FW200, Color Black S170, Special Black 550, Special Black 4A, and Printex 30 manufactured by Degussa, and Monarch 880, Regal 250R, Regal 400R, and Regal 660R manufactured by Cabot Corporation. Note that these are examples of carbon black suitable for the present invention, and the present invention is not limited thereto.

[0048] The carbon black content in the resin member is 0.001 to 0.064% by mass, preferably 0.001 to 0.032% by mass. If the content is less than 0.001% by mass, the heat generated is small even when the energy of the laser light is absorbed, so the temperature does not rise sufficiently and the welding strength of the joint between the resin members is low. If the content exceeds 0.064% by mass, the heat generated is too high, so that scorching and voids are likely to occur, and it is difficult to obtain sufficient welding strength between the resin members.

[0049] The resin member may contain other thermoplastic resins as long as the properties of the liquid crystal resin are not impaired. For example, polyphenylene sulfide resin (PPS), polyamide resin (nylon (PA)), polyolefin resin such as polyethylene resin or polypropylene resin, Examples of the resin include polystyrene resin, polymethylpentene resin, methacrylic resin, acrylic polyamide resin, ethylene vinyl alcohol (EVOH) resin, polycarbonate resin, polyester resins such as polyethylene terephthalate (PET) resin and polybutylene terephthalate (PBT) resin, polyacetal resin, polyvinyl chloride resin, polyvinylidene chloride resin, polyphenylene oxide resin, polyarylate resin, polyarylsulfone resin, and fluororesin.

[0050] Examples of polyamide resins include polyamide 6, polyamide 66, polyamide 46, polyamide 11, polyamide 12, polyamide 69, polyamide 610, polyamide 612, and polyamide 96; amorphous polyamides; high melting point polyamides; polyamide RIM, polyamide MIX6, and the like; and copolymers of two or more of these, i.e., polyamide 6 / 66 copolymer, polyamide 6 / 66 / 610 copolymer, polyamide 6 / 66 / 11 / 12 copolymer, crystalline polyamide / amorphous polyamide copolymer, and the like. The polyamide resin may also be a mixed polymer of a polyamide resin and another synthetic resin. Examples of such a mixed polymer include polyamide / polyester mixed polymer, polyamide / polyphenylene oxide mixed polymer, polyamide / polycarbonate mixed polymer, polyamide / polyolefin mixed polymer, polyamide / styrene / acrylonitrile mixed polymer, polyamide / acrylic acid ester mixed polymer, and polyamide / silicone mixed polymer. These polyamide resins may be used alone or in a mixture of two or more.

[0051] Polyphenylene sulfide resin, also known as PPS, is a polymer mainly composed of repeating units consisting of thiophenylene groups represented by (-φ-S-) [φ is a substituted or unsubstituted phenylene group]. This resin is produced by polymerizing a monomer synthesized by reacting paradichlorobenzene with an alkali sulfide under high temperature and pressure. This resin is roughly classified into two types: a straight-chain type in which the desired degree of polymerization is achieved only by the polymerization process using a polymerization aid, and a crosslinked type in which a low-molecular polymer is thermally crosslinked in the presence of oxygen. In particular, the straight-chain type is preferable because of its excellent transmittance. In addition, there is no particular limit to the melt viscosity of polyphenylene sulfide resin (PPS) as long as it can be melt-kneaded, but a PPS in the range of 5 to 2000 Pa·s is usually used, and a PPS in the range of 100 to 600 Pa·s is preferable.

[0052] Polyphenylene sulfide resin can also be used in polymer alloys. Examples include PPS / polyolefin alloys, PPS / polyamide alloys, PPS / polyester alloys, PPS / polycarbonate alloys, PPS / polyphenylene ether alloys, PPS / liquid crystal polymer alloys, PPS / polyimide alloys, and PPS / polysulfone alloys. Polyphenylene sulfide resins also have properties suitable for use in electronic parts, automobile parts, and the like.

[0053] Examples of polyester resins include polyethylene terephthalate resin obtained by polycondensation reaction of terephthalic acid and ethylene glycol, and polybutylene terephthalate resin obtained by polycondensation reaction of terephthalic acid and butylene glycol. Examples of other polyester resins include copolymers in which a part of the terephthalic acid component in the above polyester resin (for example, 15 mol% or less [for example, 0.5 to 15 mol%], preferably 5 mol% or less [for example, 0.5 to 5 mol%]) and / or a part of the ethylene glycol or butylene glycol component (for example, 15 mol% or less [for example, 0.5 to 15 mol%], preferably 5 mol% or less [for example, 0.5 to 5 mol%]) is substituted. In addition, a mixture of two or more polyester resins may be used.

[0054] The polyolefin resin is not particularly limited. Examples thereof include homopolymers of α-olefins such as ethylene, propylene, butene-1, 3-methylbutene-1, 4-methylpentene-1, octene-1, and the like, copolymers thereof, and copolymers of these with other copolymerizable unsaturated monomers (copolymers include block copolymers, random copolymers, and graft copolymers). More specific examples include polyethylene resins such as high-density polyethylene, medium-density polyethylene, low-density polyethylene, linear low-density polyethylene, ethylene-vinyl acetate copolymer, and ethylene-ethyl acrylate copolymer; polypropylene resins such as propylene homopolymer, propylene-ethylene block copolymer, or random copolymer, and propylene-ethylene-butene-1 copolymer; polybutene-1, poly-4-methylpentene-1, and the like. These polyolefin resins may be used alone or in combination of two or more. Among these, it is preferable to use polypropylene resin and / or polyethylene resin. More preferable is polypropylene resin. There is no particular limitation on this polypropylene resin, and those with a wide range of molecular weights can be used.

[0055] In addition, the polyolefin resin may contain a foaming agent in the resin itself, such as an acid-modified polyolefin modified with an unsaturated carboxylic acid or its derivative, or foamed polypropylene. The polyolefin resin may contain rubbers such as ethylene-α-olefin copolymer rubber, ethylene-α-olefin-non-conjugated diene compound copolymer (e.g., EPDM, etc.), ethylene-aromatic monovinyl compound-conjugated diene compound copolymer rubber, or hydrogenated products thereof.

[0056] Polycarbonate is a thermoplastic resin with carbonate ester bonds in the main chain, and has excellent mechanical properties, heat resistance, cold resistance, electrical properties, transparency, etc., making it a representative engineering plastic. At present, aromatic polycarbonate from bisphenol A is industrially produced. There are two manufacturing methods: the phosgene method and the ester exchange method. The chemical structure is a linear molecule in which many carbonate esters of aromatic hydrocarbons are linked together, and the molecular main chain consists of a bulky benzene nucleus and a flexible carbonate. The former gives it a high heat distortion temperature and excellent physical and mechanical properties, while the latter contributes to moldability and flexibility, but is easily hydrolyzed by alkali.

[0057] The thermoplastic resin may be a copolymer resin consisting of two or more kinds of monomers forming the thermoplastic resin. Examples of the copolymer resin include AS (acrylonitrile-styrene) copolymer resin, BBS (acrylonitrile-butadiene-styrene) copolymer resin, AES (acrylonitrile-EPDM-styrene) copolymer resin, PA-PBT copolymer, PET-PBT copolymer resin, PC-PBT copolymer resin, and PC-PA copolymer resin. Examples of the thermoplastic resin include thermoplastic elastomers such as polystyrene-based thermoplastic elastomers, polyolefin-based thermoplastic elastomers, polyurethane-based thermoplastic elastomers, and polyester-based thermoplastic elastomers; and synthetic waxes or natural waxes containing the above-mentioned resins as the main components. The molecular weight of these thermoplastic resins is not particularly limited. A plurality of different resins may be used.

[0058] When molding this resin member, various additives may be mixed as necessary and used, such as colorants, reinforcing materials, fillers, ultraviolet absorbers or light stabilizers, antioxidants, antibacterial and antifungal agents, flame retardants, auxiliary colorants, dispersants, stabilizers, plasticizers, modifiers, antistatic agents, lubricants, mold release agents, crystallization accelerators, crystal nucleating agents, etc.

[0059] Examples of colorants that can be used are not particularly limited in terms of structure or hue, so long as they do not impede laser welding of resin members. More specific examples include organic dyes and pigments such as azomethine-based, anthraquinone-based, quinacridone-based, dioxazine-based, diketopyrrolopyrrole-based, anthrapyridone-based, isoindolinone-based, indanthrone-based, perinone-based, perylene-based, indigo-based, thioindigo-based, quinophthalone-based, quinoline-based, and triphenylmethane-based dyes and pigments.

[0060] When the absorbent used in the resin part is black or dark colored, a good black resin part can be obtained by mixing a black colorant according to the hue and concentration of the absorbent. Examples of black mixed colorants include a combination of a blue colorant + a yellow colorant + a red colorant, a combination of a purple colorant + a yellow colorant, and a combination of a green colorant + a red colorant. When the absorbent is a light-colored absorbent, a resin part of each color can be obtained by appropriately combining them.

[0061] Furthermore, white pigments such as titanium oxide, zinc white, calcium carbonate, and alumina white, as well as organic white pigments, can be contained, and the colors can be adjusted from achromatic to chromatic by combining with organic dyes and pigments.

[0062] The reinforcing material is not particularly limited as long as it can be used to reinforce ordinary synthetic resins. For example, glass fiber, carbon fiber, other inorganic fibers, and organic fibers (aramid, polyphenylene sulfide resin, polyamide, polyester, etc.) can be used, and glass fiber is preferred for reinforcing resins that require transparency. The fiber length of glass fiber that can be suitably used is 2 to 15 mm, and the fiber diameter is 1 to 20 μm. There is no particular limitation on the form of the glass fiber, and it may be any of, for example, roving, milled fiber, etc. These glass fibers can be used alone or in combination of two or more types. The content is preferably 5 to 120 parts by mass with respect to 100 parts by mass of the resin member. If it is less than 5 parts by mass, it is difficult to obtain a sufficient glass fiber reinforcing effect, and if it exceeds 120 parts by mass, the moldability is likely to decrease. It is preferably 10 to 60 parts by mass, and particularly preferably 20 to 50 parts by mass.

[0063] Further, as the filler, plate-like fillers such as mica, sericite, glass flakes, etc.; silicates such as talc, kaolin, clay, wollastonite, bentonite, asbestos, alumina silicate, etc.; metal oxides such as alumina, silicon oxide, magnesium oxide, zirconium oxide, titanium oxide, etc.; carbonates such as calcium carbonate, magnesium carbonate, dolomite, etc.; sulfates such as calcium sulfate, barium sulfate, etc.; and particulate fillers such as glass beads, ceramic beads, boron nitride, silicon carbide, etc. can be added.

[0064] Examples of the ultraviolet absorber or light stabilizer include benzotriazole-based compounds, benzophenone-based compounds, salicylate-based compounds, cyanoacrylate-based compounds, benzoate-based compounds, oxalate-based compounds, hindered amine-based compounds, and nickel complex salts.

[0065] Examples of the antioxidant include phenol-based compounds, phosphorus-based compounds, sulfur-based compounds, and thioether-based compounds.

[0066] Examples of antibacterial and antifungal agents include 2-(4'-thiazolyl)benzimidazole, 10,10'-oxybisphenoxyarsine, N-(fluorodichloromethylthio)phthalimide, and bis(2-pyridylthio-1-oxide)zinc.

[0067] Examples of flame retardants include halogen-containing compounds such as tetrabromobisphenol A derivatives, hexabromodiphenyl ether, and tetrabromophthalic anhydride; phosphorus-containing compounds such as triphenyl phosphate, triphenyl phosphite, red phosphorus, and ammonium polyphosphate; nitrogen-containing compounds such as urea and guanidine; silicon-containing compounds such as silicone oil, organic silanes, and aluminum silicate; and antimony compounds such as antimony trioxide and antimony phosphate.

[0068] This resin member may be manufactured using a masterbatch of a desired colored thermoplastic resin composition. The masterbatch can be obtained by any method. For example, the masterbatch can be obtained by mixing a powder or pellet of a resin base of the masterbatch with a colorant in a mixer such as a tumbler or a super mixer, and then heating and melting the mixture in an extruder, a batch mixer, a roll mixer, or the like to pelletize or coarsely granulate the mixture.

[0069] The molding of the resin member can be carried out by various procedures that are usually performed. For example, it can be carried out by using colored pellets and molding them with a processing machine such as an extruder, an injection molding machine, or a roll mill, or by mixing transparent resin pellets or powder, a pulverized colorant, and various additives as necessary in an appropriate mixer and molding the mixture using a processing machine. For example, a colorant can be added to a monomer containing an appropriate polymerization catalyst, and the mixture can be polymerized to a desired resin, which can then be molded by an appropriate method. As the molding method, any of the commonly performed molding methods, such as injection molding, extrusion molding, compression molding, foam molding, blow molding, vacuum molding, injection blow molding, rotational molding, calendar molding, and solution casting, can be used. By such molding, resin members of various shapes can be obtained. EXAMPLES

[0070] The present invention will now be described in more detail with reference to examples, but it is needless to say that the present invention is not limited to these examples.

[0071] Example 1 (1-a) Preparation of resin parts 499.9 g of I-type liquid crystalline polyester resin (Sumitomo Chemical Co., Ltd., product name: Sumika Super LCP (registered trademark) E6007LHF, glass filler 35%) and 0.15 g of Nigrosine (Orient Chemical Industries Co., Ltd., product name: NUBIAN (registered trademark) BLACK TH-807) were placed in a stainless steel tumbler and mixed with stirring for 1 hour. The resulting mixture was molded by a conventional method using an injection molding machine (Toyo Machinery and Metals Co., Ltd., product name: Si-50) at a cylinder temperature of 310 to 360°C and a mold temperature of 80°C to produce two resin members 1 and 2 with dimensions of length 80 mm, width 50 mm, and thickness 1 mm.

[0072] (1-b) Manufacturing of laser welded parts Next, resin parts 1 and 2 were brought into contact with each other as shown in Figure 1, and a laser beam from a 50W diode laser [wavelength: 940nm continuous] (Hamamatsu Photonics) was irradiated along the interface between the butted resin parts 1 and 2, scanning 20mm at a scanning speed of 10mm / sec, resulting in an integrated laser welded body. The strength of this laser welded body was measured by a tensile strength test. (Tensile test) In accordance with JIS K7161:2014 Plastics - Test method for tensile properties, both resin members 1 and 2 of the laser welded body were pulled horizontally in the longitudinal direction in the direction in which they were separated at a test speed of 10 mm / min using a tensile tester (manufactured by Shimadzu Corporation, product name: AG-50kNE) to measure the tensile strength as the weld strength. The results are shown in Table 1.

[0073] Example 2 (2-a) Preparation of resin parts 499.7 g of I-type liquid crystalline polyester resin (Sumitomo Chemical Co., Ltd., product name: Sumika Super LCP (registered trademark) E6007LHF, glass filler 35%) and 0.3 g of Nigrosine (Orient Chemical Industries Co., Ltd., product name: NUBIAN (registered trademark) BLACK TH-807) were placed in a stainless steel tumbler and mixed with stirring for 1 hour. The resulting mixture was molded by a conventional method using an injection molding machine (Toyo Machinery and Metals Co., Ltd., product name: Si-50) at a cylinder temperature of 310 to 360°C and a mold temperature of 80°C to produce two resin members 1 and 2 with dimensions of length 80 mm x width 50 mm x thickness 1 mm.

[0074] (2-b) Manufacturing of laser welded parts Next, the resin members 1 and 2 were brought into contact with each other while being butted together as shown in Figure 1, and a laser beam from a 40 W diode laser [wavelength: 940 nm continuous] (manufactured by Hamamatsu Photonics KK) was irradiated along the interface between the butted resin members 1 and 2, scanning for 20 mm at a scanning speed of 10 mm / sec, to obtain an integrated laser welded body. The tensile strength of the obtained laser welded body was measured in the same manner as in Example 1. The results are shown in Table 1.

[0075] Example 3 (3-a) Preparation of resin parts 499.4 g of I-type liquid crystalline polyester resin (Sumitomo Chemical Co., Ltd., product name: Sumikasuper LCP (registered trademark) E6007LHF, glass filler 35%) and 0.6 g of Nigrosine (Orient Chemical Industries Co., Ltd., product name: NUBIAN (registered trademark) BLACK TH-807) were placed in a stainless steel tumbler and mixed with stirring for 1 hour. The resulting mixture was molded by a conventional method using an injection molding machine (Toyo Machinery and Metals Co., Ltd., product name: Si-50) at a cylinder temperature of 310 to 360°C and a mold temperature of 80°C to produce two resin members 1 and 2 with dimensions of length 80 mm x width 50 mm x thickness 1 mm.

[0076] (3-b) Manufacturing of laser welded parts Next, the resin members 1 and 2 were brought into contact with each other while being butted together as shown in Figure 1, and a laser beam from a 40 W diode laser [wavelength: 940 nm continuous] (manufactured by Hamamatsu Photonics KK) was irradiated along the interface between the butted resin members 1 and 2, scanning for 20 mm at a scanning speed of 10 mm / sec, to obtain an integrated laser welded body. The tensile strength of the obtained laser welded body was measured in the same manner as in Example 1. The results are shown in Table 1.

[0077] Example 4 (4-a) Preparation of resin parts 399 g of I-type liquid crystalline polyester resin (Sumitomo Chemical Co., Ltd., product name: Sumikasuper LCP (registered trademark) E6007LHF, glass filler 35%) and 0.96 g of Nigrosine (Orient Chemical Industries Co., Ltd., product name: NUBIAN (registered trademark) BLACK TH-807) were placed in a stainless steel tumbler and mixed with stirring for 1 hour. The resulting mixture was molded by a conventional method using an injection molding machine (Toyo Machinery and Metals Co., Ltd., product name: Si-50) at a cylinder temperature of 310 to 360°C and a mold temperature of 80°C to produce two resin members 1 and 2 with dimensions of length 80 mm, width 50 mm, and thickness 1 mm.

[0078] (4-b) Manufacturing of laser welded parts Next, the resin members 1 and 2 were brought into contact with each other while being butted together as shown in Figure 1, and a laser beam from a 20 W diode laser [wavelength: 940 nm continuous] (manufactured by Hamamatsu Photonics KK) was irradiated along the interface between the butted resin members 1 and 2, scanning 20 mm at a scanning speed of 10 mm / sec, to obtain an integrated laser welded body. The tensile strength of the obtained laser welded body was measured in the same manner as in Example 1. The results are shown in Table 1.

[0079] Example 5 (5-a) Preparation of resin parts 398.1 g of I-type liquid crystalline polyester resin (Sumitomo Chemical Co., Ltd., product name: Sumika Super LCP (registered trademark) E6007LHF, glass filler 35%) and 1.92 g of Nigrosine (Orient Chemical Industries Co., Ltd., product name: NUBIAN (registered trademark) BLACK TH-807) were placed in a stainless steel tumbler and mixed with stirring for 1 hour. The resulting mixture was molded by a conventional method using an injection molding machine (Toyo Machinery and Metals Co., Ltd., product name: Si-50) at a cylinder temperature of 310 to 360°C and a mold temperature of 80°C to produce two resin members 1 and 2 with dimensions of length 80 mm, width 50 mm, and thickness 1 mm.

[0080] (5-b) Manufacturing of laser welded parts Next, the resin members 1 and 2 were brought into contact with each other while being butted together as shown in Figure 1, and a laser beam from a 20 W diode laser [wavelength: 940 nm continuous] (manufactured by Hamamatsu Photonics KK) was irradiated along the interface between the butted resin members 1 and 2, scanning 20 mm at a scanning speed of 10 mm / sec, to obtain an integrated laser welded body. The tensile strength of the obtained laser welded body was measured in the same manner as in Example 1. The results are shown in Table 1.

[0081] Example 6 (6-a) Preparation of resin parts 499.9 g of I-type liquid crystal polyester resin (Sumitomo Chemical Co., Ltd., trade name: Sumika Super LCP (registered trademark) E6007LHF, glass filler 35%) and 0.15 g of Nigrosine (Orient Chemical Industries Co., Ltd., trade name: NUBIAN (registered trademark) BLACK TH-807) were placed in a stainless steel tumbler and mixed with stirring for 1 hour. The resulting mixture was molded by a conventional method using an injection molding machine (Toyo Machinery and Metals Co., Ltd., trade name: Si-50) at a cylinder temperature of 310 to 360°C and a mold temperature of 80°C to produce one resin member 1 with a length of 80 mm, a width of 50 mm, and a thickness of 1 mm.

[0082] (6-b) Preparation of resin parts 499.7 g of I-type liquid crystal polyester resin (Sumitomo Chemical Co., Ltd.'s product name: Sumika Super LCP (registered trademark) E6007LHF, glass filler 35%) and 0.3 g of Nigrosine (Orient Chemical Industries Co., Ltd.'s product name: NUBIAN (registered trademark) BLACK TH-807) were placed in a stainless steel tumbler and mixed with stirring for 1 hour. The resulting mixture was molded by a conventional method using an injection molding machine (Toyo Machinery and Metals Co., Ltd.'s product name: Si-50) at a cylinder temperature of 310 to 360°C and a mold temperature of 80°C to produce one resin member 2 with a length of 80 mm, a width of 50 mm, and a thickness of 1 mm.

[0083] (6-c) Manufacturing of laser welded parts Next, the resin members 1 and 2 were brought into contact with each other while being butted together as shown in Figure 1, and a laser beam from a 40 W diode laser [wavelength: 940 nm continuous] (manufactured by Hamamatsu Photonics KK) was irradiated along the interface between the butted resin members 1 and 2, scanning for 20 mm at a scanning speed of 10 mm / sec, to obtain an integrated laser welded body. The tensile strength of the obtained laser welded body was measured in the same manner as in Example 1. The results are shown in Table 1.

[0084] Comparative Example 1 (1-A) Preparation of resin parts 500 g of I-type liquid crystalline polyester resin (Sumitomo Chemical Co., Ltd., product name: Sumikasuper LCP (registered trademark) E6007LHF, glass filler 35%) was molded by a conventional method using an injection molding machine (Toyo Machinery and Metals Co., Ltd., product name: Si-50) at a cylinder temperature of 310 to 360°C and a mold temperature of 80°C to produce two resin members 1 and 2 measuring 80 mm in length, 50 mm in width, and 1 mm in thickness.

[0085] (1-B) Manufacturing of laser welded parts Next, the resin parts 1 and 2 were brought into contact with each other as shown in Figure 1, and a laser beam from a diode laser [wavelength: 940 nm continuous] (Hamamatsu Photonics) was irradiated along the interface between the butted resin parts 1 and 2 at an output of 10 to 80 W and a scanning speed of 10 mm / sec, scanning for 20 mm. With an output of 10 to 70 W, no laser weld was obtained, and with an output of 80 W, no laser weld was obtained and the surface was burned.

[0086] Comparative Example 2 (2-A) Preparation of resin parts 600 g of I-type liquid crystalline polyester resin (Sumitomo Chemical Co., Ltd., product name: Sumikasuper LCP (registered trademark) E6007LHF, glass filler 35%) and 0.03 g of Nigrosine (Orient Chemical Industries Co., Ltd., product name: NUBIAN (registered trademark) BLACK TH-807) were placed in a stainless steel tumbler and mixed with stirring for 1 hour. The resulting mixture was molded by a conventional method using an injection molding machine (Toyo Machinery and Metals Co., Ltd., product name: Si-50) at a cylinder temperature of 310 to 360°C and a mold temperature of 80°C to produce two resin members 1 and 2 with dimensions of length 80 mm, width 50 mm, and thickness 1 mm.

[0087] (2-B) Manufacturing of laser welded parts Next, the resin parts 1 and 2 were brought into contact with each other as shown in Figure 1, and a laser beam from a diode laser [wavelength: 940 nm continuous] (Hamamatsu Photonics) was irradiated along the interface between the butted resin parts 1 and 2 at an output of 10 to 60 W and a scanning speed of 10 mm / sec, scanning for 20 mm. With an output of 10 to 50 W, no laser weld was obtained, and with an output of 60 W, no laser weld was obtained and the surface was burned.

[0088] Comparative Example 3 (3-A) Preparation of resin parts 500 g of I-type liquid crystalline polyester resin (Sumitomo Chemical Co., Ltd., product name: Sumikasuper LCP (registered trademark) E6007LHF, glass filler 35%) and 0.05 g of Nigrosine (Orient Chemical Industries Co., Ltd., product name: NUBIAN (registered trademark) BLACK TH-807) were placed in a stainless steel tumbler and mixed with stirring for 1 hour. The resulting mixture was molded by a conventional method using an injection molding machine (Toyo Machinery and Metals Co., Ltd., product name: Si-50) at a cylinder temperature of 310 to 360°C and a mold temperature of 80°C to produce two resin members 1 and 2 with dimensions of length 80 mm x width 50 mm x thickness 1 mm. (3-B) Manufacturing of laser welded parts Next, the resin members 1 and 2 were brought into contact with each other while being butted together as shown in Figure 1, and a laser beam from a 40 W diode laser [wavelength: 940 nm continuous] (manufactured by Hamamatsu Photonics KK) was irradiated along the interface between the butted resin members 1 and 2, scanning for 20 mm at a scanning speed of 10 mm / sec, to obtain an integrated laser welded body. The tensile strength of the obtained laser welded body was measured in the same manner as in Example 1, but the strength was very low. The results are shown in Table 1.

[0089] Comparative Example 4 (4-A) Preparation of resin parts 396.2 g of I-type liquid crystalline polyester resin (Sumitomo Chemical Co., Ltd., product name: Sumikasuper LCP (registered trademark) E6007LHF, glass filler 35%) and 3.84 g of Nigrosine (Orient Chemical Industries Co., Ltd., product name: NUBIAN (registered trademark) BLACK TH-807) were placed in a stainless steel tumbler and mixed with stirring for 1 hour. The resulting mixture was molded by a conventional method using an injection molding machine (Toyo Machinery and Metals Co., Ltd., product name: Si-50) at a cylinder temperature of 310 to 360°C and a mold temperature of 80°C to produce two resin members 1 and 2 with dimensions of length 80 mm x width 50 mm x thickness 1 mm.

[0090] (4-B) Manufacturing of laser welded parts Next, the resin parts 1 and 2 were brought into contact with each other as shown in Figure 1, and a laser beam from a diode laser [wavelength: 940 nm continuous] (Hamamatsu Photonics) was irradiated along the interface between the butted resin parts 1 and 2 at an output of 5-10 W and a scanning speed of 10 mm / sec, scanning 20 mm. At an output of 5 W, no laser weld was obtained, and at an output of 10 W, no laser weld was obtained and the surface was burned.

[0091] [Table 1]

[0092] As shown in Table 1, the laser welded resin members containing an appropriate amount of nigrosine (Examples 1 to 6) exhibited high tensile strength. Furthermore, the higher the nigrosine content, the lower the output of the laser beam that allowed welding. Laser welding was possible even when the members had different nigrosine contents (Example 6). On the other hand, no laser welded member was obtained from the resin member of Comparative Example 1, which did not contain nigrosine. No laser welded member was obtained from resin members containing too little nigrosine (Comparative Examples 2 and 3) or too much (Comparative Example 4), or even if a laser welded member was obtained, the weld strength was very low.

[0093] Example 7 (7-a) Preparation of resin parts 600 g of I-type liquid crystalline polyester resin (Sumitomo Chemical Co., Ltd., product name: Sumika Super LCP (registered trademark) E6007LHF, glass filler 35%) and 0.006 g of carbon black (Mitsubishi Chemical Co., Ltd., product name: MA600) were placed in a stainless steel tumbler and mixed with stirring for 1 hour. The resulting mixture was molded by a conventional method using an injection molding machine (Toyo Machinery and Metals Co., Ltd., product name: Si-50) at a cylinder temperature of 310 to 360°C and a mold temperature of 80°C to produce two resin members 1 and 2 with dimensions of length 80 mm, width 50 mm, and thickness 1 mm.

[0094] (7-b) Manufacturing of laser welded parts Next, the resin members 1 and 2 were brought into contact with each other while being butted together as shown in Figure 1, and a laser beam from an 80 W diode laser [wavelength: 940 nm continuous] (manufactured by Hamamatsu Photonics KK) was irradiated along the interface between the butted resin members 1 and 2, scanning for 20 mm at a scanning speed of 10 mm / sec, to obtain an integrated laser welded body. The tensile strength of the obtained laser welded body was measured in the same manner as in Example 1. The results are shown in Table 2.

[0095] Example 8 (8-a) Preparation of resin parts 500 g of I-type liquid crystalline polyester resin (Sumitomo Chemical Co., Ltd., product name: Sumika Super LCP (registered trademark) E6007LHF, glass filler 35%) and 0.015 g of carbon black (Mitsubishi Chemical Co., Ltd., product name: MA600) were placed in a stainless steel tumbler and mixed with stirring for 1 hour. The resulting mixture was molded by a conventional method using an injection molding machine (Toyo Machinery and Metals Co., Ltd., product name: Si-50) at a cylinder temperature of 310 to 360°C and a mold temperature of 80°C to produce two resin members 1 and 2 with dimensions of length 80 mm, width 50 mm, and thickness 1 mm.

[0096] (8-b) Manufacturing of laser welded parts Next, the resin members 1 and 2 were brought into contact with each other while being butted together as shown in Figure 1, and a laser beam from a 70 W diode laser [wavelength: 940 nm continuous] (manufactured by Hamamatsu Photonics KK) was irradiated along the interface between the butted resin members 1 and 2, scanning for 20 mm at a scanning speed of 10 mm / sec, to obtain an integrated laser welded body. The tensile strength of the obtained laser welded body was measured in the same manner as in Example 1. The results are shown in Table 2.

[0097] Example 9 (9-a) Preparation of resin parts 500 g of I-type liquid crystalline polyester resin (Sumitomo Chemical Co., Ltd., product name: Sumika Super LCP (registered trademark) E6007LHF, glass filler 35%) and 0.04 g of carbon black (Mitsubishi Chemical Co., Ltd., product name: MA600) were placed in a stainless steel tumbler and mixed with stirring for 1 hour. The resulting mixture was molded by a conventional method using an injection molding machine (Toyo Machinery and Metals Co., Ltd., product name: Si-50) at a cylinder temperature of 310 to 360°C and a mold temperature of 80°C to produce two resin members 1 and 2 measuring 80 mm in length, 50 mm in width, and 1 mm in thickness.

[0098] (9-b) Manufacturing of laser welded parts Next, the resin members 1 and 2 were brought into contact with each other while being butted together as shown in Figure 1, and a laser beam from a 50 W diode laser [wavelength: 940 nm continuous] (manufactured by Hamamatsu Photonics KK) was irradiated along the interface between the butted resin members 1 and 2, scanning for 20 mm at a scanning speed of 10 mm / sec, to obtain an integrated laser welded body. The tensile strength of the obtained laser welded body was measured in the same manner as in Example 1. The results are shown in Table 2.

[0099] Example 10 (10-a) Preparation of resin parts 499.9 g of I-type liquid crystalline polyester resin (Sumitomo Chemical Co., Ltd., product name: Sumika Super LCP (registered trademark) E6007LHF, glass filler 35%) and 0.08 g of carbon black (Mitsubishi Chemical Co., Ltd., product name: MA600) were placed in a stainless steel tumbler and mixed with stirring for 1 hour. The resulting mixture was molded by a conventional method using an injection molding machine (Toyo Machinery and Metals Co., Ltd., product name: Si-50) at a cylinder temperature of 310 to 360°C and a mold temperature of 80°C to produce two resin members 1 and 2 with dimensions of length 80 mm, width 50 mm, and thickness 1 mm.

[0100] (10-b) Manufacturing of laser welded parts Next, the resin members 1 and 2 were brought into contact with each other while being butted together as shown in Figure 1, and a laser beam from a 30 W diode laser [wavelength: 940 nm continuous] (manufactured by Hamamatsu Photonics KK) was irradiated along the interface between the butted resin members 1 and 2, scanning for 20 mm at a scanning speed of 10 mm / sec, to obtain an integrated laser welded body. The tensile strength of the obtained laser welded body was measured in the same manner as in Example 1. The results are shown in Table 2.

[0101] Example 11 (11-a) Preparation of resin parts 499.8 g of I-type liquid crystalline polyester resin (Sumitomo Chemical Co., Ltd., product name: Sumika Super LCP (registered trademark) E6007LHF, glass filler 35%) and 0.16 g of carbon black (Mitsubishi Chemical Co., Ltd., product name: MA600) were placed in a stainless steel tumbler and mixed with stirring for 1 hour. The resulting mixture was molded by a conventional method using an injection molding machine (Toyo Machinery and Metals Co., Ltd., product name: Si-50) at a cylinder temperature of 310 to 360°C and a mold temperature of 80°C to produce two resin members 1 and 2 with dimensions of length 80 mm, width 50 mm, and thickness 1 mm.

[0102] (11-b) Manufacturing of laser welded parts Next, the resin members 1 and 2 were brought into contact with each other while being butted together as shown in Figure 1, and a laser beam from a 30 W diode laser [wavelength: 940 nm continuous] (manufactured by Hamamatsu Photonics KK) was irradiated along the interface between the butted resin members 1 and 2, scanning for 20 mm at a scanning speed of 10 mm / sec, to obtain an integrated laser welded body. The tensile strength of the obtained laser welded body was measured in the same manner as in Example 1. The results are shown in Table 2.

[0103] Example 12 (12-a) Preparation of resin parts 399.7 g of I-type liquid crystalline polyester resin (Sumitomo Chemical Co., Ltd., product name: Sumika Super LCP (registered trademark) E6007LHF, glass filler 35%) and 0.256 g of carbon black (Mitsubishi Chemical Co., Ltd., product name: MA600) were placed in a stainless steel tumbler and mixed with stirring for 1 hour. The resulting mixture was molded by a conventional method using an injection molding machine (Toyo Machinery and Metals Co., Ltd., product name: Si-50) at a cylinder temperature of 310 to 360°C and a mold temperature of 80°C to produce two resin members 1 and 2 with dimensions of length 80 mm, width 50 mm, and thickness 1 mm.

[0104] (12-b) Manufacturing of laser welded parts Next, the resin members 1 and 2 were brought into contact with each other while being butted together as shown in Figure 1, and a laser beam from a 20 W diode laser [wavelength: 940 nm continuous] (manufactured by Hamamatsu Photonics KK) was irradiated along the interface between the butted resin members 1 and 2, scanning 20 mm at a scanning speed of 10 mm / sec, to obtain an integrated laser welded body. The tensile strength of the obtained laser welded body was measured in the same manner as in Example 1. The results are shown in Table 2.

[0105] Example 13 (13-a) Preparation of resin parts 500 g of I-type liquid crystal polyester resin (Sumitomo Chemical Co., Ltd.'s product name: Sumika Super LCP (registered trademark) E6007LHF, glass filler 35%) and 0.015 g of carbon black (Mitsubishi Chemical Co., Ltd.'s product name: MA600) were placed in a stainless steel tumbler and mixed with stirring for 1 hour. The resulting mixture was molded by a conventional method using an injection molding machine (Toyo Machinery & Metals Co., Ltd.'s product name: Si-50) at a cylinder temperature of 310 to 360°C and a mold temperature of 80°C to produce one resin member 1 with a length of 80 mm, a width of 50 mm, and a thickness of 1 mm.

[0106] (13-b) Preparation of resin parts 500 g of I-type liquid crystal polyester resin (Sumitomo Chemical's product name: Sumika Super LCP (registered trademark) E6007LHF, glass filler 35%) and 0.04 g of carbon black (Mitsubishi Chemical's product name: MA600) were placed in a stainless steel tumbler and mixed by stirring for 1 hour. The mixture obtained was molded by a conventional method using an injection molding machine (Toyo Machinery and Metals' product name: Si-50) at a cylinder temperature of 310 to 360°C and a mold temperature of 80°C to produce one resin member 2 with a length of 80 mm, a width of 50 mm, and a thickness of 1 mm.

[0107] (13-c) Manufacturing of laser welded parts Next, the resin members 1 and 2 were brought into contact with each other while being butted together as shown in Figure 1, and a laser beam from a 60 W diode laser [wavelength: 940 nm continuous] (manufactured by Hamamatsu Photonics KK) was irradiated along the interface between the butted resin members 1 and 2, scanning for 20 mm at a scanning speed of 10 mm / sec, to obtain an integrated laser welded body. The tensile strength of the obtained laser welded body was measured in the same manner as in Example 1. The results are shown in Table 2.

[0108] Comparative Example 5 (5-A) Preparation of resin parts 600 g of I-type liquid crystalline polyester resin (Sumitomo Chemical Co., Ltd., product name: Sumika Super LCP (registered trademark) E6007LHF, glass filler 35%) and 0.003 g of carbon black (Mitsubishi Chemical Co., Ltd., product name: MA600) were placed in a stainless steel tumbler and mixed with stirring for 1 hour. The resulting mixture was molded by a conventional method using an injection molding machine (Toyo Machinery and Metals Co., Ltd., product name: Si-50) at a cylinder temperature of 310 to 360°C and a mold temperature of 80°C to produce two resin members 1 and 2 with dimensions of length 80 mm, width 50 mm, and thickness 1 mm.

[0109] (5-B) Manufacturing of laser welded parts Next, the resin members 1 and 2 were brought into contact with each other as shown in Figure 1, and a laser beam from a 60 W diode laser [wavelength: 940 nm continuous] (manufactured by Hamamatsu Photonics KK) was irradiated along the interface between the butted resin members 1 and 2, scanning for 20 mm at a scanning speed of 10 mm / sec, to obtain an integrated laser welded body. The tensile strength of the obtained laser welded body was measured in the same manner as in Example 1, but the strength was very low. The results are shown in Table 2.

[0110] Comparative Example 6 (6-A) Preparation of resin parts 399.5 g of I-type liquid crystalline polyester resin (Sumitomo Chemical Co., Ltd., product name: Sumika Super LCP (registered trademark) E6007LHF, glass filler 35%) and 0.512 g of carbon black (Mitsubishi Chemical Co., Ltd., product name: MA600) were placed in a stainless steel tumbler and mixed with stirring for 1 hour. The resulting mixture was molded by a conventional method using an injection molding machine (Toyo Machinery and Metals Co., Ltd., product name: Si-50) at a cylinder temperature of 310 to 360°C and a mold temperature of 80°C to produce two resin members 1 and 2 with dimensions of length 80 mm, width 50 mm, and thickness 1 mm.

[0111] (6-B) Manufacturing of laser welded parts Next, the resin parts 1 and 2 were brought into contact with each other as shown in Figure 1, and a laser beam from a diode laser [wavelength: 940 nm continuous] (Hamamatsu Photonics) was irradiated along the interface between the butted resin parts 1 and 2 at an output of 10-20 W and a scanning speed of 10 mm / sec, scanning 20 mm. At an output of 10 W, no laser weld was obtained, and at an output of 20 W, no laser weld was obtained and the surface was burned.

[0112] (Comparative Example) (7-A) Preparation of resin parts 399 g of I-type liquid crystalline polyester resin (Sumitomo Chemical Co., Ltd., product name: Sumika Super LCP (registered trademark) E6007LHF, glass filler 35%) and 1.024 g of carbon black (Mitsubishi Chemical Co., Ltd., product name: MA600) were placed in a stainless steel tumbler and mixed with stirring for 1 hour. The resulting mixture was molded by a conventional method using an injection molding machine (Toyo Machinery and Metals Co., Ltd., product name: Si-50) at a cylinder temperature of 310 to 360°C and a mold temperature of 80°C to produce two resin members 1 and 2 with dimensions of length 80 mm, width 50 mm, and thickness 1 mm.

[0113] (7-B) Manufacturing of laser welded parts Next, the resin parts 1 and 2 were brought into contact with each other as shown in Figure 1, and a laser beam from a diode laser [wavelength: 940 nm continuous] (Hamamatsu Photonics) was irradiated along the interface between the butted resin parts 1 and 2 at an output of 10-20 W and a scanning speed of 10 mm / sec, scanning 20 mm. At an output of 10 W, no laser weld was obtained, and at an output of 20 W, no laser weld was obtained and the surface was burned.

[0114] [Table 2]

[0115] As shown in Table 2, the laser welded resin members containing an appropriate amount of carbon black (Examples 7 to 13) exhibited high tensile strength. Furthermore, the higher the carbon black content, the lower the output of the laser beam that allowed welding. Laser welding was possible even when the members had different carbon black contents (Example 13). On the other hand, when the resin member contained too little carbon black (Comparative Example 5) or too much carbon black (Comparative Examples 6 and 7), no laser welded member was obtained, or even if one was obtained, the weld strength was very low.

[0116] Example 14 (14-a) Preparation of resin parts 499.9 g of I-type liquid crystal polyester resin (Sumitomo Chemical Co., Ltd., trade name: Sumika Super LCP (registered trademark) E6007LHF, glass filler 35%) and 0.15 g of Nigrosine (Orient Chemical Industries Co., Ltd., trade name: NUBIAN (registered trademark) BLACK TH-807) were placed in a stainless steel tumbler and mixed with stirring for 1 hour. The resulting mixture was molded by a conventional method using an injection molding machine (Toyo Machinery and Metals Co., Ltd., trade name: Si-50) at a cylinder temperature of 310 to 360°C and a mold temperature of 80°C to produce one resin member 1 with a length of 80 mm, a width of 50 mm, and a thickness of 1 mm.

[0117] (14-b) Preparation of resin parts 500 g of I-type liquid crystal polyester resin (Sumitomo Chemical's product name: Sumika Super LCP (registered trademark) E6007LHF, glass filler 35%) and 0.015 g of carbon black (Mitsubishi Chemical's product name: MA600) were placed in a stainless steel tumbler and mixed by stirring for 1 hour. The mixture obtained was molded by a conventional method using an injection molding machine (Toyo Machinery and Metals' product name: Si-50) at a cylinder temperature of 310 to 360°C and a mold temperature of 80°C to produce one resin member 2 with a length of 80 mm, a width of 50 mm, and a thickness of 1 mm.

[0118] (14-c) Manufacturing of laser welded parts Next, the resin members 1 and 2 were brought into contact with each other while being butted together as shown in Figure 1, and a laser beam from a 50 W diode laser [wavelength: 940 nm continuous] (manufactured by Hamamatsu Photonics KK) was irradiated along the interface between the butted resin members 1 and 2, scanning for 20 mm at a scanning speed of 10 mm / sec, to obtain an integrated laser welded body. The tensile strength of the obtained laser welded body was measured in the same manner as in Example 1. The results are shown in Table 3.

[0119] Example 15 (15-a) Preparation of resin parts 499.9 g of I-type liquid crystal polyester resin (Sumitomo Chemical Co., Ltd., trade name: Sumika Super LCP (registered trademark) E6007LHF, glass filler 35%) and 0.15 g of Nigrosine (Orient Chemical Industries Co., Ltd., trade name: NUBIAN (registered trademark) BLACK TH-807) were placed in a stainless steel tumbler and mixed with stirring for 1 hour. The resulting mixture was molded by a conventional method using an injection molding machine (Toyo Machinery and Metals Co., Ltd., trade name: Si-50) at a cylinder temperature of 310 to 360°C and a mold temperature of 80°C to produce one resin member 1 with a length of 80 mm, a width of 50 mm, and a thickness of 1 mm.

[0120] (15-b) Preparation of resin parts 500 g of I-type liquid crystal polyester resin (Sumitomo Chemical's product name: Sumika Super LCP (registered trademark) E6007LHF, glass filler 35%) and 0.04 g of carbon black (Mitsubishi Chemical's product name: MA600) were placed in a stainless steel tumbler and mixed by stirring for 1 hour. The mixture obtained was molded by a conventional method using an injection molding machine (Toyo Machinery and Metals' product name: Si-50) at a cylinder temperature of 310 to 360°C and a mold temperature of 80°C to produce one resin member 2 with a length of 80 mm, a width of 50 mm, and a thickness of 1 mm.

[0121] (15-c) Manufacturing of laser welded parts Next, the resin members 1 and 2 were brought into contact with each other while being butted together as shown in Figure 1, and a laser beam from a 50 W diode laser [wavelength: 940 nm continuous] (manufactured by Hamamatsu Photonics KK) was irradiated along the interface between the butted resin members 1 and 2, scanning for 20 mm at a scanning speed of 10 mm / sec, to obtain an integrated laser welded body. The tensile strength of the obtained laser welded body was measured in the same manner as in Example 1. The results are shown in Table 3.

[0122] Example 16 (16-a) Preparation of resin parts 398.1 g of I-type liquid crystal polyester resin (Sumitomo Chemical Co., Ltd., trade name: Sumika Super LCP (registered trademark) E6007LHF, glass filler 35%) and 1.92 g of Nigrosine (Orient Chemical Industries Co., Ltd., trade name: NUBIAN (registered trademark) BLACK TH-807) were placed in a stainless steel tumbler and mixed with stirring for 1 hour. The resulting mixture was molded by a conventional method using an injection molding machine (Toyo Machinery and Metals Co., Ltd., trade name: Si-50) at a cylinder temperature of 310 to 360°C and a mold temperature of 80°C to produce one resin member 1 with a length of 80 mm, a width of 50 mm, and a thickness of 1 mm.

[0123] (16-b) Preparation of resin parts 600 g of I-type liquid crystal polyester resin (Sumitomo Chemical's product name: Sumika Super LCP (registered trademark) E6007LHF, glass filler 35%) and 0.006 g of carbon black (Mitsubishi Chemical's product name: MA600) were placed in a stainless steel tumbler and mixed by stirring for 1 hour. The resulting mixture was molded by a conventional method using an injection molding machine (Toyo Machinery & Metals' product name: Si-50) at a cylinder temperature of 310 to 360°C and a mold temperature of 80°C to produce one resin member 1 with a length of 80 mm, a width of 50 mm, and a thickness of 1 mm.

[0124] (16-c) Manufacturing of laser welded parts Next, the resin members 1 and 2 were brought into contact with each other while being butted together as shown in Figure 1, and a laser beam from a 50 W diode laser [wavelength: 940 nm continuous] (manufactured by Hamamatsu Photonics KK) was irradiated along the interface between the butted resin members 1 and 2, scanning for 20 mm at a scanning speed of 10 mm / sec, to obtain an integrated laser welded body. The tensile strength of the obtained laser welded body was measured in the same manner as in Example 1. The results are shown in Table 3.

[0125] Comparative Example 8 (8-A) Preparation of resin parts 499.9 g of I-type liquid crystal polyester resin (Sumitomo Chemical Co., Ltd., trade name: Sumika Super LCP (registered trademark) E6007LHF, glass filler 35%) and 0.15 g of Nigrosine (Orient Chemical Industries Co., Ltd., trade name: NUBIAN (registered trademark) BLACK TH-807) were placed in a stainless steel tumbler and mixed with stirring for 1 hour. The resulting mixture was molded by a conventional method using an injection molding machine (Toyo Machinery and Metals Co., Ltd., trade name: Si-50) at a cylinder temperature of 310 to 360°C and a mold temperature of 80°C to produce one resin member 1 with a length of 80 mm, a width of 50 mm, and a thickness of 1 mm.

[0126] (8-B) Preparation of resin parts 500 g of I-type liquid crystal polyester resin (Sumitomo Chemical Co., Ltd., product name: Sumika Super LCP (registered trademark) E6007LHF, glass filler 35%) was placed in a stainless steel tumbler and mixed with stirring for 1 hour. The mixture obtained was molded by a conventional method using an injection molding machine (Toyo Machinery & Metals Co., Ltd., product name: Si-50) at a cylinder temperature of 310 to 360°C and a mold temperature of 80°C to produce one resin member 2 with a length of 80 mm, a width of 50 mm, and a thickness of 1 mm.

[0127] (8-C) Manufacturing of laser welded parts Next, the resin parts 1 and 2 were brought into contact with each other as shown in Figure 1, and a laser beam from a diode laser [wavelength: 940 nm continuous] (Hamamatsu Photonics) was irradiated along the interface between the butted resin parts 1 and 2 at an output of 10 to 70 W and a scanning speed of 10 mm / sec, scanning for 20 mm. With an output of 10 to 60 W, no laser weld was obtained, and with an output of 70 W, a burn occurred on the surface.

[0128] Comparative Example 9 (9-A) Preparation of resin parts 500 g of I-type liquid crystal polyester resin (Sumitomo Chemical Co., Ltd., product name: Sumika Super LCP (registered trademark) E6007LHF, glass filler 35%) was placed in a stainless steel tumbler and mixed with stirring for 1 hour. The mixture obtained was molded by a conventional method using an injection molding machine (Toyo Machinery & Metals Co., Ltd., product name: Si-50) at a cylinder temperature of 310 to 360°C and a mold temperature of 80°C to produce one resin member 2 with a length of 80 mm, a width of 50 mm, and a thickness of 1 mm.

[0129] (9-B) Preparation of resin parts 500 g of I-type liquid crystal polyester resin (Sumitomo Chemical's product name: Sumika Super LCP (registered trademark) E6007LHF, glass filler 35%) and 0.04 g of carbon black (Mitsubishi Chemical's product name: MA600) were placed in a stainless steel tumbler and mixed by stirring for 1 hour. The mixture obtained was molded by a conventional method using an injection molding machine (Toyo Machinery and Metals' product name: Si-50) at a cylinder temperature of 310 to 360°C and a mold temperature of 80°C to produce one resin member 2 with a length of 80 mm, a width of 50 mm, and a thickness of 1 mm.

[0130] (9-C) Manufacturing of laser welded parts Next, the resin members 1 and 2 were brought into contact with each other as shown in Figure 1, and a laser beam from a 60 W diode laser [wavelength: 940 nm continuous] (manufactured by Hamamatsu Photonics KK) was irradiated along the interface between the butted resin members 1 and 2, scanning for 20 mm at a scanning speed of 10 mm / sec, to obtain an integrated laser welded body. The tensile strength of the obtained laser welded body was measured in the same manner as in Example 1, but the strength was very low. The results are shown in Table 3.

[0131] Comparative Example 10 (10-A) Preparation of resin parts 500 g of I-type liquid crystalline polyester resin (Sumitomo Chemical Co., Ltd., product name: Sumika Super LCP (registered trademark) E6007LHF) was placed in a stainless steel tumbler and mixed with stirring for 1 hour. The mixture obtained was molded by a conventional method using an injection molding machine (Toyo Machinery & Metals Co., Ltd., product name: Si-50) at a cylinder temperature of 310 to 360°C and a mold temperature of 80°C to produce one resin member 2 with a length of 80 mm, a width of 50 mm, and a thickness of 1 mm.

[0132] (10-B) Preparation of resin parts 498 g of I-type liquid crystal polyester resin (Sumitomo Chemical Co., Ltd.'s product name: Sumika Super LCP (registered trademark) E6007LHF, glass filler 35%) and 2 g of carbon black (Mitsubishi Chemical Co., Ltd.'s product name: MA600) were placed in a stainless steel tumbler and mixed by stirring for 1 hour. The resulting mixture was molded by a conventional method using an injection molding machine (Toyo Machinery & Metals Co., Ltd.'s product name: Si-50) at a cylinder temperature of 310 to 360°C and a mold temperature of 80°C to produce one resin member 2 with a length of 80 mm, a width of 50 mm, and a thickness of 1 mm.

[0133] (10-C) Manufacturing of laser welded parts Next, the resin parts 1 and 2 were brought into contact with each other as shown in Figure 1, and a laser beam from a diode laser [wavelength: 940 nm continuous] (Hamamatsu Photonics) was irradiated along the interface between the butted resin parts 1 and 2 at an output of 10-20 W and a scanning speed of 10 mm / sec, scanning 20 mm. At an output of 10 W, no laser weld was obtained, and at an output of 20 W, no laser weld was obtained and the surface was burned.

[0134] [Table 3]

[0135] As shown in Table 3, a laser welded product could be obtained without any problems even when a resin member containing nigrosine was combined with a resin member containing carbon black (Examples 14 to 16). A laser welded product could also be obtained when a resin member with a high concentration of nigrosine was combined with a resin member with a low concentration of carbon black (Example 16). On the other hand, a laser welded product could not be obtained when a resin member containing no laser light absorbent was combined with a resin member containing a laser light absorbent, or even if a laser welded product was obtained, the weld strength was low (Comparative Examples 8 to 10). The resin member prepared in 10-B contains a high concentration of carbon black, which corresponds to the laser light absorbing member in the laser welding of overlapping layers. A laser welded product could not be obtained even when a member having such high laser light absorption was combined with a resin member containing no laser light absorbent.

[0136] (Example 17) (17-a) Preparation of resin parts 499.9 g of type II liquid crystalline polyester resin (manufactured by Ueno Pharmaceutical Co., Ltd., product name: UENO LCP (registered trademark) 3030G, glass filler 30%) and 0.15 g of nigrosine (manufactured by Orient Chemical Industries Co., Ltd., product name: NUBIAN (registered trademark) BLACK TH-807) were placed in a stainless steel tumbler and mixed with stirring for 1 hour. The resulting mixture was molded by a conventional method using an injection molding machine (manufactured by Toyo Machinery and Metals Co., Ltd., product name: Si-50) at a cylinder temperature of 310 to 360°C and a mold temperature of 80°C to produce two resin members 1 and 2 with dimensions of length 80 mm, width 50 mm, and thickness 1 mm.

[0137] (17-b) Manufacturing of laser welded parts Next, the resin members 1 and 2 were brought into contact with each other as shown in Figure 1, and a laser beam from a 60 W diode laser [wavelength: 940 nm continuous] (manufactured by Hamamatsu Photonics KK) was irradiated along the interface between the butted resin members 1 and 2, scanning for 20 mm at a scanning speed of 10 mm / sec, to obtain an integrated laser welded body. The tensile strength of the obtained laser welded body was measured in the same manner as in Example 1. The results are shown in Table 4.

[0138] (Example 18) (18-a) Preparation of resin parts 499.7 g of type II liquid crystalline polyester resin (manufactured by Ueno Pharmaceutical Co., Ltd., product name: UENO LCP (registered trademark) 3030G, glass filler 30%) and 0.3 g of nigrosine (manufactured by Orient Chemical Industries Co., Ltd., product name: NUBIAN (registered trademark) BLACK TH-807) were placed in a stainless steel tumbler and mixed with stirring for 1 hour. The resulting mixture was molded by a conventional method using an injection molding machine (manufactured by Toyo Machinery and Metals Co., Ltd., product name: Si-50) at a cylinder temperature of 310 to 360°C and a mold temperature of 80°C to produce two resin members 1 and 2 measuring 80 mm in length, 50 mm in width, and 1 mm in thickness. (18-b) Manufacturing of laser welded parts Next, the resin members 1 and 2 were brought into contact with each other while being butted together as shown in Figure 1, and a laser beam from a 40 W diode laser [wavelength: 940 nm continuous] (manufactured by Hamamatsu Photonics KK) was irradiated along the interface between the butted resin members 1 and 2, scanning for 20 mm at a scanning speed of 10 mm / sec, to obtain an integrated laser welded body. The tensile strength of the obtained laser welded body was measured in the same manner as in Example 1. The results are shown in Table 4.

[0139] (Example 19) (19-a) Preparation of resin parts 500 g of type II liquid crystalline polyester resin (manufactured by Ueno Pharmaceutical Co., Ltd., product name: UENO LCP (registered trademark) 3030G, glass filler 30%) and 0.015 g of carbon black (manufactured by Mitsubishi Chemical Corporation, product name: MA600) were placed in a stainless steel tumbler and mixed with stirring for 1 hour. The resulting mixture was molded by a conventional method using an injection molding machine (manufactured by Toyo Machinery and Metals Co., Ltd., product name: Si-50) at a cylinder temperature of 310 to 360°C and a mold temperature of 80°C to produce two resin members 1 and 2 measuring 80 mm in length, 50 mm in width, and 1 mm in thickness.

[0140] (19-b) Manufacturing of laser welded parts Next, the resin members 1 and 2 were brought into contact with each other as shown in Figure 1, and a laser beam from a 60 W diode laser [wavelength: 940 nm continuous] (manufactured by Hamamatsu Photonics KK) was irradiated along the interface between the butted resin members 1 and 2, scanning for 20 mm at a scanning speed of 10 mm / sec, to obtain an integrated laser welded body. The tensile strength of the obtained laser welded body was measured in the same manner as in Example 1. The results are shown in Table 4.

[0141] (Example 20) (20-a) Preparation of resin parts 500 g of type II liquid crystalline polyester resin (manufactured by Ueno Pharmaceutical Co., Ltd., product name: UENO LCP (registered trademark) 3030G, glass filler 30%) and 0.04 g of carbon black (manufactured by Mitsubishi Chemical Corporation, product name: MA600) were placed in a stainless steel tumbler and mixed with stirring for 1 hour. The resulting mixture was molded by a conventional method using an injection molding machine (manufactured by Toyo Machinery and Metals Co., Ltd., product name: Si-50) at a cylinder temperature of 310 to 360°C and a mold temperature of 80°C to produce two resin members 1 and 2 with dimensions of length 80 mm, width 50 mm, and thickness 1 mm.

[0142] (20-b) Manufacturing of laser welded parts Next, the resin members 1 and 2 were brought into contact with each other while being butted together as shown in Figure 1, and a laser beam from a 50 W diode laser [wavelength: 940 nm continuous] (manufactured by Hamamatsu Photonics KK) was irradiated along the interface between the butted resin members 1 and 2, scanning for 20 mm at a scanning speed of 10 mm / sec, to obtain an integrated laser welded body. The tensile strength of the obtained laser welded body was measured in the same manner as in Example 1. The results are shown in Table 4.

[0143] Comparative Example 11 (11-A) Preparation of resin parts Two resin members 1 and 2 measuring 80 mm in length, 50 mm in width, and 1 mm in thickness were produced by molding 600 g of type II liquid crystalline polyester resin (manufactured by Ueno Pharmaceutical Co., Ltd., product name: UENO LCP (registered trademark) 3030G, glass filler 30%) in a conventional manner using an injection molding machine (manufactured by Toyo Machinery and Metals Co., Ltd., product name: Si-50) at a cylinder temperature of 310 to 360°C and a mold temperature of 80°C.

[0144] (11-B) Manufacturing of laser welded parts Next, the resin parts 1 and 2 were brought into contact with each other as shown in Figure 1, and a laser beam from a diode laser [wavelength: 940 nm continuous] (Hamamatsu Photonics) was irradiated along the interface between the butted resin parts 1 and 2 at an output of 10 to 70 W and a scanning speed of 10 mm / sec, scanning for 20 mm. With an output of 10 to 60 W, no laser weld was obtained, and with an output of 70 W, a burn occurred on the surface.

[0145] [Table 4]

[0146] Example 21 (21-a) Preparation of resin parts 499.9 g of type II liquid crystalline polyester resin (manufactured by Polyplastics Co., Ltd., product name: LAPEROS (registered trademark) E130i, glass filler 30%) and 0.15 g of Nigrosine (manufactured by Orient Chemical Industries Co., Ltd., product name: NUBIAN (registered trademark) BLACK TH-807) were placed in a stainless steel tumbler and mixed with stirring for 1 hour. The resulting mixture was molded by a conventional method using an injection molding machine (manufactured by Toyo Machinery and Metals Co., Ltd., product name: Si-50) at a cylinder temperature of 310 to 360°C and a mold temperature of 80°C to produce two resin members 1 and 2 measuring 80 mm in length, 50 mm in width, and 1 mm in thickness.

[0147] (21-b) Manufacturing of laser welded parts Next, the resin members 1 and 2 were brought into contact with each other as shown in Figure 1, and a laser beam from a 50 W diode laser [wavelength: 940 nm continuous] (manufactured by Hamamatsu Photonics KK) was irradiated along the interface between the butted resin members 1 and 2, scanning for 20 mm at a scanning speed of 10 mm / sec, to obtain an integrated laser welded body. The tensile strength of the obtained laser welded body was measured in the same manner as in Example 1. The results are shown in Table 5.

[0148] Example 22 (22-a) Preparation of resin parts 499.7 g of type II liquid crystalline polyester resin (manufactured by Polyplastics Co., Ltd., product name: LAPEROS (registered trademark) E130i, glass filler 30%) and 0.3 g of Nigrosine (manufactured by Orient Chemical Industries Co., Ltd., product name: NUBIAN (registered trademark) BLACK TH-807) were placed in a stainless steel tumbler and mixed with stirring for 1 hour. The resulting mixture was molded by a conventional method using an injection molding machine (manufactured by Toyo Machinery and Metals Co., Ltd., product name: Si-50) at a cylinder temperature of 310 to 360°C and a mold temperature of 80°C to produce two resin members 1 and 2 measuring 80 mm in length, 50 mm in width, and 1 mm in thickness.

[0149] (22-b) Manufacturing of laser welded parts Next, the resin members 1 and 2 were brought into contact with each other as shown in Figure 1, and a laser beam from a 50 W diode laser [wavelength: 940 nm continuous] (manufactured by Hamamatsu Photonics KK) was irradiated along the interface between the butted resin members 1 and 2, scanning for 20 mm at a scanning speed of 10 mm / sec, to obtain an integrated laser welded body. The tensile strength of the obtained laser welded body was measured in the same manner as in Example 1. The results are shown in Table 5.

[0150] (Example 23) (23-a) Preparation of resin parts 500 g of type II liquid crystalline polyester resin (manufactured by Polyplastics Co., Ltd., product name: LAPEROS (registered trademark) E130i, glass filler 30%) and 0.015 g of carbon black (manufactured by Mitsubishi Chemical Co., Ltd., product name: MA600) were placed in a stainless steel tumbler and mixed with stirring for 1 hour. The resulting mixture was molded by a conventional method using an injection molding machine (manufactured by Toyo Machinery and Metals Co., Ltd., product name: Si-50) at a cylinder temperature of 310 to 360°C and a mold temperature of 80°C to produce two resin members 1 and 2 measuring 80 mm in length, 50 mm in width, and 1 mm in thickness.

[0151] (23-b) Manufacturing of laser welded parts Next, the resin members 1 and 2 were brought into contact with each other while being butted together as shown in Figure 1, and a laser beam from a 60 W diode laser [wavelength: 940 nm continuous] (manufactured by Hamamatsu Photonics KK) was irradiated along the interface between the butted resin members 1 and 2, scanning for 20 mm at a scanning speed of 10 mm / sec, to obtain an integrated laser welded body. The tensile strength of the obtained laser welded body was measured in the same manner as in Example 1. The results are shown in Table 5.

[0152] (Example 24) (24-a) Preparation of resin parts 500 g of type II liquid crystalline polyester resin (manufactured by Polyplastics Co., Ltd., product name: LAPEROS (registered trademark) E130i, glass filler 30%) and 0.04 g of carbon black (manufactured by Mitsubishi Chemical Co., Ltd., product name: MA600) were placed in a stainless steel tumbler and mixed with stirring for 1 hour. The resulting mixture was molded by a conventional method using an injection molding machine (manufactured by Toyo Machinery and Metals Co., Ltd., product name: Si-50) at a cylinder temperature of 310 to 360°C and a mold temperature of 80°C to produce two resin members 1 and 2 measuring 80 mm in length, 50 mm in width, and 1 mm in thickness.

[0153] (24-b) Manufacturing of laser welded parts Next, the resin members 1 and 2 were brought into contact with each other as shown in Figure 1, and a laser beam from a 40 W diode laser [wavelength: 940 nm continuous] (manufactured by Hamamatsu Photonics KK) was irradiated along the interface between the butted resin members 1 and 2, scanning for 20 mm at a scanning speed of 10 mm / sec, to obtain an integrated laser welded body. The tensile strength of the obtained laser welded body was measured in the same manner as in Example 1. The results are shown in Table 5.

[0154] Comparative Example 12 (12-A) Preparation of resin parts Two resin members 1 and 2 measuring 80 mm in length, 50 mm in width, and 1 mm in thickness were produced by a conventional method using an injection molding machine (Toyo Machinery and Metals Co., Ltd., product name: Si-50) at a cylinder temperature of 310 to 360°C and a mold temperature of 80°C. An amount of 600 g of a type II liquid crystalline polyester resin (manufactured by Polyplastics Co., Ltd., product name: LAPEROS (registered trademark) E130i, glass filler 30%) was molded.

[0155] (12-B) Manufacturing of laser welded parts Next, the resin parts 1 and 2 were brought into contact with each other as shown in Figure 1, and a laser beam from a diode laser [wavelength: 940 nm continuous] (Hamamatsu Photonics) was irradiated along the interface between the butted resin parts 1 and 2 at an output of 10 to 80 W and a scanning speed of 10 mm / sec, scanning for 20 mm. With an output of 10 to 70 W, no laser weld was obtained, and with an output of 80 W, no laser weld was obtained and the surface was burned.

[0156] [Table 5]

[0157] As is clear from Tables 4 and 5, the type II liquid crystalline polyester could also be used to obtain laser welded articles by adding a laser beam absorbent, as was the case with the type I liquid crystalline polyester (Examples 17 to 24). However, the type II liquid crystalline polyester alone, without adding a laser beam absorbent, could not obtain laser welded articles (Comparative Examples 11 and 12). [Industrial Applicability]

[0158] The laser-welded article of the present invention is useful for a variety of applications, such as electric and electronic equipment, precision machinery equipment, office equipment, automobile and vehicle parts, building materials, packaging materials, furniture, and daily necessities. [Explanation of symbols]

[0159] 1 and 2 are the resin parts, 3 is the laser light, and 4 is the welded part.

Claims

1. A laser welded body in which resin members containing a thermoplastic resin and a laser beam absorbent are integrated by being laser welded at least at a part of a butt joint where at least a part of the ends of the resin members are butted against each other, The thermoplastic resin contains a liquid crystalline resin, The laser welded article is characterized in that the laser beam absorbent is contained in the resin workpiece in an amount of 0.001% by mass to 0.48% by mass.

2. 2. The laser welded article according to claim 1, wherein the thermoplastic resin contains a liquid crystal polyester.

3. 2. The laser welded article according to claim 1, wherein the laser beam absorbent is nigrosine and / or carbon black.

4. 2. The laser welded product according to claim 1, wherein the laser beam absorbent is nigrosine and is contained in the resin member in an amount of 0.03% by mass to 0.48% by mass.

5. 2. The laser welded product according to claim 1, wherein the laser beam absorbent is carbon black, and is contained in the resin member in an amount of 0.001% by mass to 0.064% by mass.

6. 2. The laser welded product according to claim 1, wherein the resin member is a single member or a plurality of members.

7. 2. The laser welded product according to claim 1, wherein the resin members are a plurality of members, and the laser beam absorbent in at least one of the resin members is nigrosine.

8. 2. The laser welded product according to claim 1, wherein the resin members are a plurality of members, and the laser beam absorbent in at least one of the resin members is carbon black.

Citation Information

Patent Citations

  • Laser welding liquid crystal resin composition and its molded article

    JP2004292526A

  • Hollow molded body and method for manufacturing the same

    JP2013203026A

  • Laser welded material

    WO2007034978A1